Influencia del porcentaje de carbono equivalente del acero estructural soldado mediante proceso GMAW en la soldabilidad evaluada según el código AWS D1.1 - Aguirre Gutiérrez, Félix Dilber (2019)
The influence of the percentage of carbon equivalent of structural steel welded by the GMAW process on the weldability evaluated by AWS code D1.1-2015 of the American Welding Society was studied, which specifies that tensile strength should not be less than the minimum of the specified tensile range of the base metal used and hardnesses in the heat-affected zone of less than 350 HV. The results obtained show that there is a significant effect of the percentage of carbon equivalent of structural steel welded by the GMAW process on weldability. All three types of steel have good weldability and it is possible to record qualified welding procedures to the specifications stated in this paper. The best properties are obtained with micro alloyed steel DOMEX and ASTM A572. The higher strength with lower carbon content is due to the addition of small amounts of Niobium, Titanium and Vanadium in these steels.